The Hydrogeochemical Model of "YR" Geothermal Field, East Java - Rachmalia, Yunisa; Haryanto, Agus Didit; Hutabarat, Johanes; Abdillah, Yuniar Zhafira (Journal of Geological Sciences and Applied Geology, 2023)
The YR Geothermal Field is located in East Java. This field is associated with an active volcano, implying a potential for a high enthalpy geothermal system. This field is still in the exploration phase, but no drilling has been conducted yet. Thus, insights into the geothermal system are obtained through geochemical analyses of geothermal manifestations. Geochemical analyses were performed on hot spring water samples to determine the characteristics, processes, origin, and fluid flow of the geothermal system. The research results indicate that the warm springs have temperatures ranging from 29.4 to 54.8°C, with a nearly neutral pH (6.14-6.44) and high contents of HCO3 (457-1150 mg/kg), Na (77.7-255 mg/kg), and Mg (37.4-110 mg/kg). Therefore, it can be concluded that all the warm springs fall into the bicarbonate type with immature conditions, indicating no direct association with the reservoir. The upflow zone is interpreted to be at the peak of Mount 7, while the outflow zones are in areas A, B, and C. The fluids flow from the upflow zone, then condense and advectively flow down the slope, experiencing dilution and reactions with rocks before emerging as outflows in the western and north-western areas.